ACUTE APPENDICITIS IN PREGNANCY – DIAGNOSTIC AND THERAPEUTIC CHALLENGES - Jan Palmi,; Elżbieta Bebrysz,; Karolina Dębek-Kalinowska,; Piotr Bartnik,; Jarosław Baran,; Ida Dunder,; Magdalena Koss,; Mateusz Biszewski,; Aleksandra Drabik,; Weronika Ziomek, (International Journal of Innovative Technologies in Social Science, 2025)
Background: Acute appendicitis during pregnancy is one of the most common non-obstetric surgical conditions in pregnant women. However, due to the ambiguous symptoms that may be presented, an accurate diagnosis can be delayed or misinterpreted as a result of pregnancy-related changes.Aim: The aim of this article is to highlight the challenges involved in diagnosing and treating acute appendicitis in pregnant women.Methods: A review of scientific articles published on Google Scholar and PubMed from 2015 to 2025.Results: Acute appendicitis in pregnancy presents with identical symptoms or mimics several other diseases, not only obstetric conditions. Surgical treatment is recommended, but there are no clear guidelines favoring either laparoscopic or open methods. Magnetic resonance imaging (MRI) is the most accurate imaging modality for diagnosing acute appendicitis. Laboratory diagnostics do not provide definitive evidence for appendicitis in pregnancy.Conclusion: It is essential to be aware of the numerous ways acute appendicitis can present in pregnancy and to remain critical of an initially proposed diagnosis. The choice of surgical treatment largely depends on the experience and skill of the physician. Therefore, continuous education is necessary to understand the challenges associated with this condition.